High sensitivity and selectivity microwave biosensor using biofunctionalized differential resonant array implemented in LTCC for Escherichia coli detection. (28th February 2023) - Piekarz, Ilona; Sorocki, Jakub; Górska, Sabina; Bartsch, Heike; Rydosz, Artur; Smolarz, Robert; Wincza, Krzysztof; Gruszczynski, Slawomir
Highlights: A novel method for label-free detection of Escherichia coli introduced relying on microwave resonator array biosensor for improved sensitivity and probability of bacteria detection. Low-Temperature Co-Fired Ceramics technology is employed for fabrication due to its quasi-3D structure capability and ease of biofunctionalization with polyclonal antibodies for increased sensing robustness and selective response. A demonstrator developed exhibiting five distinct resonances in a frequency range of 4 – 6 GHz operating in differential transmission mode. Experiment carried out for of various concentrations of Escherichia coli and a non-specific high concentration of Lactobacillus rhamnosus LOCK 0919 proved the low detection threshold and selective response capability. Abstract: A novel method for label-free detection of Escherichia coli relying on microwave sensing is proposed. A transmission-type differential resonator array biosensor covered with polyclonal anti- Escherichia coli antibodies is introduced providing a robust response with high sensitivity for detecting bacteria presence due to resonant operation combined. The high selectivity is given by the presence of specific bacteria-binding antibodies. Low-Temperature Co-Fired Ceramics technology is proposed to be used for implementation to take advantage of its quasi-three-dimensional fabrication capability. The proposed sensing structure operates in a frequency range of 4 – 6 GHz with five distinct resonances increasing the probability of bacteria detection presence. The developed sensor was experimentally validated by measurements of various concentrations of Escherichia coli along with measurement of a non-specific high concentration of Lactobacillus rhamnosus LOCK 0919. The obtained results prove the performance and suitability of the proposed biosensor for biomedical applications.